2004
DOI: 10.1161/01.cir.0000145170.22652.51
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Induced Cholesterol Lowering and Plaque Regression After 6 Months of Magnetic Resonance Imaging–Monitored Therapy

Abstract: Background-Statin therapy reduces adverse outcomes, with a minimal decrease in vessel stenosis. Magnetic resonance imaging (MRI) noninvasively detects atherosclerotic plaque (AP) reduction. We hypothesized that statin-induced AP regression can be monitored by MRI and detected earlier than previously reported and is significantly associated with its lipid-lowering effect. Methods and Results-APs in thoracic aorta were measured by combined surface/transesophageal MRI in 27 patients (treated with simvastatin 20 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(88 citation statements)
references
References 39 publications
4
82
2
Order By: Relevance
“…Earlier reports have shown a reduction in either the event rate or the vessel wall area after a pharmacological intervention disproportionately to or in the absence of luminal changes (10 -12). In a follow-up study of patients on statin therapy, no luminal changes were observed in the thoracic aorta by MRI after a short treatment period of six months, but plaque volume and area decreased significantly (12). Prolonged treatment has been shown to significantly increase the luminal area with a range of 4% to 6% in both the aorta and the carotid artery, along with a regression in the vessel wall thickness and area of up to 20% (11).…”
Section: Discussionmentioning
confidence: 96%
“…Earlier reports have shown a reduction in either the event rate or the vessel wall area after a pharmacological intervention disproportionately to or in the absence of luminal changes (10 -12). In a follow-up study of patients on statin therapy, no luminal changes were observed in the thoracic aorta by MRI after a short treatment period of six months, but plaque volume and area decreased significantly (12). Prolonged treatment has been shown to significantly increase the luminal area with a range of 4% to 6% in both the aorta and the carotid artery, along with a regression in the vessel wall thickness and area of up to 20% (11).…”
Section: Discussionmentioning
confidence: 96%
“…Clinical trials have shown that LDL apheresis, which removes plasma LDL particles physically, can improve endothelium-dependent vasomotion through acute reduction in serum cholesterol levels [68]. Cholesterol lowering modifies atherosclerotic-plaque biology, thereby decreasing vascular inflammation and leukocyte activation [69]. Thus, statins can improve endothelial function through reduction in serum cholesterol levels.…”
Section: Statins and Vascular Dysfunctionmentioning
confidence: 99%
“…Studies with carotid MRI demonstrated an interstudy reproducibility of 4.4% 85 . A number of serial studies in humans have assessed CMR in the longitudinal measurement of aortic and carotid atheroma [86][87][88][89][90] .…”
Section: Cardiovascular Magnetic Resonancementioning
confidence: 99%
“…Atherosclerotic plaque in thoracic aorta were measured by combined surface/transesophageal MRI in 27 patients (treated with simvastatin 20 to 80 mg daily) before and after 6 months of therapy 89 . Plaque volume and luminal dimensions were measured from 6 cross sections used to construct a 2.4-cm 3D volume of the aorta that included plaque and lumen.…”
Section: Cardiovascular Magnetic Resonancementioning
confidence: 99%